Molecular Mechanisms Linking ALS/FTD and Psychiatric Disorders, the Potential Effects of Lithium - Limanaqi, Fiona; Biagioni, Francesca; Ryskalin, Larisa; Busceti, Carla L.; Fornai, Francesco (Frontiers in Cellular Neuroscience, 2019)
Altered proteostasis, endoplasmic reticulum (ER) stress, abnormal unfolded protein response (UPR), mitochondrial dysfunction and autophagy impairment are interconnected events, which contribute to the pathogenesis of amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). In recent years, the mood stabilizer lithium was shown to potentially modify ALS/FTD beyond mood disorder-related pathology. The effects of lithium are significant in ALS patients carrying genetic variations in the UNC13 presynaptic protein, which occur in ALS/FTD and psychiatric disorders as well. In the brain, lithium modulates a number of biochemical pathways involved in synaptic plasticity, proteostasis, and neuronal survival. By targeting UPR-related events, namely ER stress, excitotoxicity and autophagy dysfunction, lithium produces plastic effects. These are likely to relate to neuroprotection, which was postulated for mood and motor neuron disorders. In the present manuscript, we try to identify and discuss potential mechanisms through which lithium copes concomitantly with ER stress, UPR and autophagy dysfunctions related to UNC13 synaptic alterations and aberrant RNA and protein processing. This may serve as a paradigm to provide novel insights into the neurobiology of ALS/FTD featuring early psychiatric disturbances.